Subacute cutaneous lupus erythematosus triggered by sintilimab: a case report - Zhang, Chenxi; Zhang, Xiaoying; Liang, Jiali; Liu, Yifei; Chen, Jialong; Wang, Qi; Li, Changxing (Frontiers in Immunology, 2025)
Immune checkpoint inhibitors (ICIs) have become a standard treatment for various cancers, but their use is often associated with immune-related adverse events (irAEs), including cutaneous irAEs (cirAEs). Here, we report a rare case of subacute cutaneous lupus erythematosus (SCLE) induced by sintilimab, a PD-1 inhibitor, in a 30-year-old woman undergoing neoadjuvant chemo-immunotherapy for gastric cancer. The patient presented with erythema, macules, papules, and vesicles, with positive ANA (108U/mL) and strongly positive anti-SSA/Ro. After discontinuation of sintilimab and treatment with corticosteroids, hydroxychloroquine, and intravenous immunoglobulin (IVIG), her symptoms improved. This case represents the first reported instance of drug-induced lupus caused by sintilimab and emphasizes the importance of distinguishing between paraneoplastic lupus and ICI-induced lupus.